Capnography and the Bispectral Index—Their Role in Pediatric Sedation: A Brief Review - Maria Sammartino; Barbara Volpe; Fabio Sbaraglia; Rossella Garra; Alessandro D'Addessi (International Journal of Pediatrics)
Sedation in children is increasingly emerging as a minimally invasive technique that may be associated with local anaesthesia or diagnostic and therapeutic procedures which do not necessarily require general anaesthesia. Standard monitoring requirements are not sufficient to ensure an effective control of pulmonary ventilation and deep sedation. Capnography in pediatric sedation assesses the effect of different drugs on the occurrence of respiratory failure and records early indicators of respiratory impairment. The Bispectral index (BIS) allows the reduction of dose requirements of anaesthetic drugs, the reduction in the time to extubation and eye opening, and the reduction in the time to discharge. In the field of pediatric sedation, capnography should be recommended to prevent respiratory complications, particularly in spontaneous ventilation. The use of the BIS index, however, needs further investigation due to a lack of evidence, especially in infants. In this paper, we will investigate the role of capnography and the BIS index in improving monitoring standards in pediatric sedation.